LEMBAGA PENDIDIKAN ISLAM PESANTREN - Nindi Aliska Nasution (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2020)
What is the importance of us knowing Islamic educational institutions such as Islamic boarding schools? So in fact the Islamic boarding school is the oldest Islamic education institution in Indonesia, currently still making important contributions in the social and religious fields. Islamic boarding school as an educational institution that has strong roots (in digenous) in the Muslim community Islamic Education for the first time in Indonesia. The position of this research is the study of the journey of Islamic boarding school that is able to maintain and also maintain its continuity as the first Islamic educational institution and has various educational models that have multiple aspects. Islam, buildings of Islamic boarding schools or educational facilities owned, Islamic boarding schools have 5 types based on the availability of facilities and infrastructure owned by the pesantren itself. While the next is based on the curriculum, the pesantren is divided into three, namely the first is a traditional pesantren (salafiyah), the second is a modern pesantren (khalaf or asriyah) and third is a comprehensive pesantren (combination). Pesantren has five elements, namely the first is the mosque, the second kyai, the third pondok, the four santri, and the fifth is the recitation using the yellow book (tafaqquh fi al-din). For the main core in the discussion in this article is to further discuss the history, development, and education system of Islamic boarding schools.